ANALISIS PUCUK MEMENUHI SYARAT (PMS) DAN UJI ORGANOLEPTIK TEH HIJAU - Jasmine, Tiara Adinda; Rahmadhia, Safinta Nurindra (Jurnal Gizi dan Pangan Soedirman, 2024)
Product quality is very important to ensure that the products produced are of high quality and safe for consumers. Therefore, product quality control is carried out on raw materials, namely qualified shoot analysis. In addition to ensuring the quality of raw materials, organoleptic testing is also carried out on the final product to assess the overall quality. The purpose of this study is to determine whether the quality control of green tea products is in accordance with the company's operational standards (SOP) or not. Qualified shoot analysis is carried out in accordance with the standards of PT Chakra Dewata Tea Plantation. There are 3 parameters, namely Qualified Shoots (PMS), Unqualified Shoots (PTMS), and Damaged. Organoleptic tests are carried out in accordance with the company's quality standards which refer to SNI 3945: 2016 green tea quality requirements. Organoleptic test quality characteristics include appearance, taste, liquor, and In Fussion parameters. The results of observations on the analysis of qualified shoots PMS parameters afdeling flat kiara has the highest average of 37.19%, PTMS afdeling gunung maud has the highest average of 62.97%, then damaged parameters with the highest average found in afdeling flat kiara which is 5.50%. The average grading results on BT #8033, SM 315, and Fanning 58 tea types are C/2.6/36/c; C/2.7/37/c; and C/2.8/38/c, respectively.